Applications of liposomes and lipid nanoparticles in cancer therapy: current advances and prospects - Zhe Cheng; Huichao Huang; Meilong Yin; Huaizheng Liu (Experimental Hematology & Oncology)
Abstract Liposomes and lipid nanoparticles are common lipid-based drug delivery systems and play important roles in cancer treatment and vaccine manufacture. Although significant progress has been made with these lipid-based nanocarriers in recent years, efficient clinical translation of active targeted liposomal nanocarriers remains extremely challenging. In this review, we focus on targeted liposomes, stimuli-responsive strategy and combined therapy in cancer treatment. We also summarize advances of liposome and lipid nanoparticle applications in nucleic acid delivery and tumor vaccination. In addition, we discuss limitations and challenges in the clinical translation of these lipid nanomaterials and make recommendations for the future research in cancer therapy. Graphical Abstract